ENGLISH LEARNING STRATEGIES USED BY THE STUDENTS IN ENGLISH EDUCATION DEPARTMENT IN SOLVING THEIR LEARNING DIFFICULTIES - ELLI MARLIANA; MARLISA MARLISA (Universitas Mahasaraswati K. Mataram, 2023)
This study focuses on the learning strategies used by students majoring in English Education in Overcoming Learning at STKIP Paracendekia NW Sumbawa. The purpose of this study was to determine the strategies applied and the difficulties faced by fourth semester students majoring in English education. This research is qualitative research. Researchers used two instruments to obtain the required data, namely: observation and interviews. Based on the data obtained from the second instrument used, the following findings were obtained. First, in the process of learning English, students with high predicate also experience learning difficulties (the most dominant learning difficulty faced when learning English were the limitation of vocabulary, differences in speakers’ accent, grammar, and pronunciation respectively). Second, successful students use not only single learning strategies but they use mixed learning strategies including memory, cognitive, compensatory, metacognitive, affective and social strategies.